Mergers, Investment Decisions and Internal Organisation - Albert Banal-Esta\~nol; Ines Macho-Stadler; Jo Seldeslachts (Center for Economic Studies and ifo Institute (CESifo), 2003)
We analyse the effects of investment decisions and firms' internal organisation on the efficiency and stability of horizontal mergers. In our framework economies of scale are endogenous and there might be internal conflict within merged firms. We show that often stable mergers do not lead to more e.ciency and may even lead to efficiency losses. These mergers lead to lower total welfare, suggesting that a regulator should be careful in assuming that possible efficiency gains of a merger will be effectively realised. Moreover, the paper offers a possible explanation for merger failures.
Keywords: 330; horizontal mergers; investment; efficiency gains; internal conflict